Psychological Factors of Subjective Well-Being of Ballet Dancers - Malysheva, Karine; Dymova, Daryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
Ballet the possibility to evolve personally in many ways: emotionally, physically and intellectually, owing to its synthetic nature. However, it requires specific personal traits from the performer. These traits could be a crucial factor in the subsequent professional success of a performer. At times, when physical potential data becomes more and more examinable, the influence of performers’ personal attributes on subjective welfare and their objective сareer accomplishments is still largely unstudied. This influence may determine the specific peculiarities of working with performance artists, in cases of providing psychological aid. It might also amend the awareness-raising activities among ballet school students. The present study explores the influence of individual psychological factors on the welfare of ballet dancers. We conducted a data collection where participants completed various types of questionnaires, such as the Wellbeing-Activities-Mood questionnaire, The Big Five Locator, Body Awareness Questionnaire, Emotional Intelligence Test (the technique of Nicholas Hall) Mindful Attention Awareness Scale (MAAS). The correlation analysis revealed that conscientiousness, emotional intelligence and mindfulness rates affect positively on the mental well-being of ballet artists. Nevertheless, mindfulness does not correlate with body awareness and openness to experience and correlates negatively with neuroticism. Conscientiousness is a salient factor for wellbeing and activity but it neither impacts on mood nor correlates with body awareness. In a series of moderated regression analyses, it was revealed that body awareness's impact on mental well-being is mediated by openness to experience. The openness to experience and body awareness were proved to be positive factors for increasing mental well-being under the influence of personal attributes.
Keywords: ballet; body image; health; subjective well-being; dance